Post Annealing Treatment Of TiO2 Nanotubes For Defective Black Oxide Formation And Application In Heavy Metal Removal - Guan, Min Li (Universiti Sains Malaysia, 2022)
Environmental pollution by wastewater due to presence of chromium ions is one of the serious issues around the world owing to its toxicity and non-biodegradability. Wastewater treatment can be done by photocatalytic process in the presence of TiO2 as photocatalyst. However, TiO2 can only be activated under ultraviolet radiation owing to its wide band gap. Producing defective oxide via hydrogenation will create mid-gap states to narrow the band gap and allow generation of charge carriers by sunlight. Thus, the objective of this project is to assess the effectiveness of pristine and defective black TiO2 nanotubes for removal of Cr(VI) ions. The synthesis of TiO2 nanotubes is performed via anodization with different anodization voltage, followed by annealing in air. Two sets of defective black TiO2 nanotubes are prepared: (i) hydrogenation after annealing in air and (ii) hydrogenation after anodization without annealing in air. Increment in diameter of nanotubes is observed when anodization voltage increased. The presence of anatase phase is confirmed in nanotubes after annealing. TiO2 nanotubes subjected to annealing in air and hydrogenation show the lowest recombination of charge carriers due to presence of oxygen vacancies and Ti3+ ions. For different anodization voltage, the highest Cr(VI) removal efficiency is achieved by air-annealed + hydrogenated TiO2 nanotubes synthesized at 60 V with 43.43% under sunlight irradiation. For different annealing conditions, TiO2 nanotubes subjected to both annealing in air and hydrogenation show highest removal efficiency of 42.23%.